Synthesis and stability of strongly acidic benzamide derivatives - Diness, Frederik; Bjerrum, Niels J.; Begtrup, Mikael (Beilstein Journal of Organic Chemistry, 2018)
Reactivity studies of strong organic acids based on the replacement of one or both of the oxygens in benzoic acids with the trifluoromethanesulfonamide group are reported. Novel derivatives of these types of acids were synthesized in good yields. The generated N-triflylbenzamides were further functionalized through cross-coupling and nucleophilic aromatic substitution reactions. All compounds were stable in dilute aqueous solutions. Studies of stability under acidic and basic conditions are also reported.
Keywords: benzoic acid; cross-coupling; hydrolysis; SNAr; trifluoromethanesulfonamide

(untitled) - Akiyama, T. (Chem. Rev., 2007)

(untitled) - Akiyama, T.; Mori, K. (Chem. Rev., 2015)

(untitled) - Peighambardoust, S. J.; Rowshanzamir, S.; Amjadi, M. (Int. J. Hydrogen Energy, 2010)

(untitled) - Miyaura, N.; Suzuki, A. (Chem. Rev., 1995)

(untitled) - Suzuki, A. (J. Organomet. Chem., 1999)

(untitled) - Dehe, D.; Munstein, I.; Reis, A.; Thiel, W. R. (J. Org. Chem., 2011)

(untitled) - Keipour, H.; Hosseini, A.; Afsari, A.; Oladee, R.; Khalilzadeh, M. A.; Ollevier, T. (Can. J. Chem., 2016)

(untitled) - Hansch, C.; Leo, A.; Taft, R. W. (Chem. Rev., 1991)

(untitled) - Yagupolskii, L. M.; Shelyazhenko, S. V.; Maletina, I. I.; Petrik, V. N.; Rusanov, E. B.; Chernega, A. N. (Eur. J. Org. Chem., 2001)

(untitled) - Yagupolskii, L. M.; Petrik, V. N.; Kondratenko, N. V.; Sooväli, L.; Kaljurand, I.; Leito, I.; Koppel, I. A. (J. Chem. Soc., Perkin Trans. 2, 2002)

(untitled) - Koppel, I. A.; Burk, P.; Koppel, I.; Leito, I. (J. Am. Chem. Soc., 2002)

(untitled) - Leito, I.; Kaljurand, I.; Koppel, I. A.; Yagupolskii, L. M.; Vlasov, V. M. (J. Org. Chem., 1998)

(untitled) - Raamat, E.; Kaupmees, K.; Ovsjannikov, G.; Trummal, A.; Kütt, A.; Saame, J.; Koppel, I.; Kaljurand, I.; Lipping, L.; Rodima, T.; Pihl, V.; Koppel, I. A.; et al. (J. Phys. Org. Chem., 2013)

(untitled) - Trummal, A.; Lipping, L.; Kaljurand, I.; Koppel, I. A.; Leito, I. (J. Phys. Chem. A, 2016)

(untitled) - Lowe, J. A., III; Drozda, S. E.; McLean, S.; Bryce, D. K.; Crawford, R. T.; Zorn, S.; Morrone, J.; Appleton, T. A.; Lombardo, F. (Bioorg. Med. Chem. Lett., 1995)

(untitled) - Hamada, Y.; Abdel-Rahman, H.; Yamani, A.; Nguyen, J.-T.; Stochaj, M.; Hidaka, K.; Kimura, T.; Hayashi, Y.; Saito, K.; Ishiurac, S.; Kiso, Y. (Bioorg. Med. Chem. Lett., 2008)

(untitled) - Cervi, G.; Magnaghi, P.; Asa, D.; Avanzi, N.; Badari, A.; Borghi, D.; Caruso, M.; Cirla, A.; Cozzi, L.; Felder, E.; Galvani, A.; Gasparri, F.; et al. (J. Med. Chem., 2014)

(untitled) - Althaus, J.; Hake, T.; Hanekamp, W.; Lehr, M. (J. Enzyme Inhib. Med. Chem., 2016)

(untitled) - Talanov, V. S.; Talanova, G. G.; Bartsch, R. A. (Tetrahedron Lett., 2000)

(untitled) - Talanov, V. S.; Talanova, G. G.; Gorbunova, M. G.; Bartsch, R. A. (J. Chem. Soc., Perkin Trans. 2, 2002)

(untitled) - Talanov, V. S.; Talanova, G. G.; Gorbunova, M. G.; Bartsch, R. A. (Tetrahedron Lett., 2002)

(untitled) - Surowiec, M.; Custelcean, R.; Surowiec, K.; Bartsch, R. A. (Tetrahedron, 2009)

(untitled) - Yang, Y.; Arora, G.; Fernandez, F. A.; Crawford, J. D.; Surowiec, K.; Lee, E. K.; Bartsch, R. A. (Tetrahedron, 2011)

(untitled) - Boston, A. L.; Lee, E. K.; Surowiec, K.; Gega, J.; Bartsch, R. A. (Tetrahedron, 2012)

(untitled) - Zhou, H.; Connery, K. E.; Bartsch, R. A.; Moyer, B. A.; Haverlock, T. J.; Delmau, L. H. (Solvent Extr. Ion Exch., 2013)

(untitled) - Hendrickson, J. B.; Bergeron, R.; Giga, A.; Sternbach, D. (J. Am. Chem. Soc., 1973)

(untitled) - Hendrickson, J. B.; Bergeron, R. (Tetrahedron Lett., 1973)

(untitled) - Benati, L.; Nanni, D.; Spagnolo, P. (J. Org. Chem., 1999)

(untitled) - Pampín, M. C.; Estévez, J. C.; Estévez, R. J.; Maestro, M.; Castedo, L. (Tetrahedron, 2003)

(untitled) - Shainyan, B. A.; Tolstikova, L. L.; Bel'skikh, A. V. (Russ. J. Org. Chem., 2008)

(untitled) - Moskalik, M. Y.; Meshcheryakov, V. I.; Shainyan, B. A. (Russ. J. Org. Chem., 2009)

(untitled) - Cody, J. A.; Ahmed, I.; Tusch, D. J. (Tetrahedron Lett., 2010)

(untitled) - Wu, C.; Li, P.; Shi, X.; Pan, X.; Wu, J. (Acta Crystallogr., Sect. E: Struct. Rep. Online, 2011)

(untitled) - Wu, X.; Rönn, R.; Gossas, T.; Larhed, M. (J. Org. Chem., 2005)

(untitled) - Urriolabeitia, E. P.; Laga, E.; Cativiela, C. (Beilstein J. Org. Chem., 2012)

(untitled) - Petrova, E.; Rasina, D.; Jirgensons, A. (Eur. J. Org. Chem., 2017)

(untitled) - Yagupolskii, L. M.; Shelyazhenko, S. V.; Maletina, I. I.; Sokolenko, L. V.; Chernega, A. N.; Rusanov, E. B.; Tsymbal, I. F. (J. Fluorine Chem., 2007)

(untitled) - Yagupolskii, L. M.; Maletina, I. I.; Sokolenko, L. V.; Vlasenko, Y. G.; Buth, S. A. (J. Fluorine Chem., 2008)

(untitled) - Yagupolskii, L. M.; Maletina, I. I.; Sokolenko, L. V.; Vlasenko, Y. G.; Drozdova, M. V.; Polovinko, V. V. (J. Fluorine Chem., 2010)

(untitled) - Asensio, J. A.; Sánchez, E. M.; Gómez-Romero, P. (Chem. Soc. Rev., 2010)

(untitled) - Diness, F.; Fairlie, D. P. (Angew. Chem., Int. Ed., 2012)

(untitled) - Diness, F.; Begtrup, M. (Org. Lett., 2014)

(untitled) - Jacobsen, C. B.; Meldal, M.; Diness, F. (Chem. – Eur. J., 2017)

(untitled) - Wang, J.-T.; Wainright, J. S.; Savinell, R. F.; Litt, M. (J. Appl. Electrochem., 1996)